Coping with the `Security-Development Nexus': The European Community's Instrument for Stability - Rationale and potential - Stefan Gänzle (Deutsches Institut für Entwicklungspolitik (DIE), 2009)
Challenges to security and development policy alike, such as fragile states, natural disasters and post-conflict reconstruction, are unlikely to respect the institutional boundaries or delimitation of competences of the European Union's complex system of governance. This holds true for the `grey area' that exists between traditional foreign/security and development policies. Since 2007, the Instrument for Stability (IfS) constitutes the European Community's main instrument for addressing what has been called the `security-development nexus'. It is a broadly mandated and flexible policy tool for rapidly funding assistance to countries in situations of (emerging) crisis and natural disaster. Thus, the IfS provides the Community with additional financial capacities in crisis management. While not fundamentally changing the institutional set-up of the EU's external relations, the IfS has contributed to removing legal obstacles and to clarifying actors' roles at the interface of foreign and development policies.
Keywords: 330